Swedish electoral data: EU-parliament election 1999 - Statistics Sweden (Statistics Sweden, 1999)
Election returns for all municipals in Sweden. Includes information on the total number of persons entitled to vote in the EU-parliament election 1995,and separately the number of immigrants who have not become citizens of Sweden, but were entitled to vote in this election, number of persons who actually voted, number of blank votes, and number of valid and invalid ballots respectively.

Valresultat för samtliga kommuner i Sverige. Innehåller uppgifter om bland annat antal röstberättigade i Europaparlamentsvalet 1995, antalet icke svenska medborgare i Sverige som var röstberättigade, valdeltagande, antal blanka röster samt antal giltiga och ogiltiga röster.
Svenska valdata: EU-parlamentsvalet 1999
Keywords: elections; val; election data; valdata; european parliament; europaparlamentet; european parliament elections; europaparlamentsval; Elections; Val; International politics and organisations; Internationell politik och organisationer; Social Sciences; Samhällsvetenskap